Exploring research gaps of Ar-Rahnu in Malaysia: An analysis using Maqasid Al-Shariah principles - Mohd Rozie Mohd Damit (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to examine the socio-economic impact, customer protection, and ethical compliance of Ar-Rahnu (Islamic pawnbroking) in Malaysia, aligning the system with Maqasid Al-Shariah principles. Through a thorough review of existing literature, it assesses Ar-Rahnu's historical development, growth, accessibility, factors contributing to popularity, and adherence to ethical standards and customer protection measures.Method — The study utilizes a comprehensive literature review and in-depth analysis of Maqasid Al-Shariah principles, evaluating Ar-Rahnu's alignment. Regulatory frameworks and initiatives supporting Islamic finance and Ar-Rahnu in Malaysia are also examined, highlighting the system's growth and prominence beyond traditional banks.Result — The study identifies critical research gaps in Ar-Rahnu and its impact on customers' religious consciousness and financial practices, role in providing financial assistance during emergencies and poverty alleviation, level of financial literacy among customers, gender dynamics, and ethical conduct of operators.Contribution — The paper makes a significant academic contribution through its innovative approach of comprehensively applying the Maqasid Al-Shariah framework to identify research gaps in Ar-Rahnu within the context of Malaysia. By doing so, it offers a unique perspective on the subject. Moreover, the research offers a clear roadmap that can be utilized by policymakers and stakeholders to align Ar-Rahnu with Islamic ethical principles. This alignment has the potential to not only enhance the system's socio-economic impact and customer protection measures but also to promote financial inclusion. Furthermore, by safeguarding the integrity of the system, this approach contributes to the overall robustness of the financial ecosystem.